2006
DOI: 10.1093/jb/mvj092
|View full text |Cite
|
Sign up to set email alerts
|

Association of Advanced Glycation End Products with A549 Cells, a Human Pulmonary Epithelial Cell Line, Is Mediated by a Receptor Distinct from the Scavenger Receptor Family and RAGE

Abstract: Cellular interactions with advanced glycation end products (AGE)-modified proteins are known to induce several biological responses, not only endocytic uptake and degradation, but also the induction of cytokines and growth factors, combined responses that may be linked to the development of diabetic vascular complications. In this study we demonstrate that A549 cells, a human pulmonary epithelial cell line, possess a specific binding site for AGE-modified bovine serum albumin (AGE-BSA) (K(d) = 27.8 nM), and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
2
17
1
Order By: Relevance
“…The observed RAGE-banding patterns from these colonic cells were virtually identical with that detected from lung epithelial cell A549 (Fig. 1), in which RAGE expression has been reported previously (38). Expression of RAGE in another colonic epithelial cell, Caco2, was also detected in the experiments (data not shown) (39).…”
Section: Rage Is Expressed In Human Intestinal Epitheliumsupporting
confidence: 87%
See 1 more Smart Citation
“…The observed RAGE-banding patterns from these colonic cells were virtually identical with that detected from lung epithelial cell A549 (Fig. 1), in which RAGE expression has been reported previously (38). Expression of RAGE in another colonic epithelial cell, Caco2, was also detected in the experiments (data not shown) (39).…”
Section: Rage Is Expressed In Human Intestinal Epitheliumsupporting
confidence: 87%
“…Due to the critical role of RAGE in regulating diabetes-associated chronic inflammations, most research on RAGE has been focused on diabetes-related organs and cells. Although several studies have reported RAGE expression in some epithelial cells, including eye epithelial cells (55,56), lung epithelial cells (38), and skin cells (57), so far there is no direct evidence of RAGE in the intestinal epithelium, in particular under inflammatory conditions. In this study, we demonstrated that RAGE is expressed in both cultured human intestinal epithelial cells and normal and inflammatory intestinal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Fig. 9B, Western blot analysis showed that RAGE is highly expressed on A549 cells, a human pulmonary epithelial cell line, as reported previously (Nakano et al, 2006). We confirmed that AGE-2 and AGE-3 at 100 g/ml Fig.…”
Section: Involvement Of Ifn-␥ and Tnf-␣ In The Effectsupporting
confidence: 90%
“…However, the 13 C NMR spectrum (in CDCl 3 at 22 or 40 1C) of 1 showed 24 resolved peaks, which lacked one carbon atom. During the process of investigation, we found that a methylene signal of C-22 was not observed in the above 13 C NMR spectra. On the other hand, the signals of H-22 and C-22 were clearly visible when the NMR data were acquired in pyridine-d 5 at -35 1C (see Table 2).…”
Section: Isolation Procedures For Nbri17671 (1)mentioning
confidence: 94%
“…The organic layer was dried over Na 2 SO 4 and concentrated to dryness. The resulting residue was purified by HPLC (column: Inertsil ODS, GL Sciences, Tokyo, Japan; 20 mmÂ250 mm, eluent: 60-100% CH 3 Compound 2 was obtained as a complex mixture of tautomers, 11 and the 1 H and 13 C NMR signals depicted above are those of the predominant enol form as shown in Figure 2. A new antitumor compound, NBRI17671 M Kawada et al…”
Section: Synthesismentioning
confidence: 99%